Antipyretic properties of ethanol, hexane and aquoeus extaction of Ficus deltoidea leaves on rats. - Nur Zafirah binti Mohd Khir. (2010, 2010)
In Malaysia, Ficus deltoidea is locally known as Mas Cotek had been traditionally used for various therapeutic purpose such as for regulating blood pressure, cholesterol and blood sugar level, and also treat migraines. The objective for this study is to evaluate the characteristic of anti-pyretic for ethanol, hexane and aqueous extract of F. deltoidea. 77 healthy male Spraque-Dawley with the average body weight between 150-200g rats was used as animal model in this study. The rats were divided into 11 groups of 7 members each. From the beginning, leaves of F. deltoidea had been dried, grinded and extracted into ethanol, hexane and aqueous extract. Initially, the rectal temperature of each group of rats was taken by using a digital thermometer (0 hour). Pyrexia was induced subcutaneously injected with 10 mg/kg of 20% (W/V) brewer’s yeast suspension into animal’s dorsum region. After 19 hours of inducer injection, and again the rectal temperature was measured (19 hour). Only rats that showed an increase in temperature of at least 0.70 C were used for experiments. Rats were pretreated intraperitoneally with 50, 100 and 200 mg/kg Ficus deltoidea of each extract, 5% Tween 80, 10 mg/kg of ibuprofen, respectively according to the group. For the final record , the temperature was measured at 1, 2,3,4 and 5 hr (20, 21, 22, 23 and 24 hour) after been treated. The results were expressed as mean ± S.E.M and analyzed statistically using the Repeated Measured followed by Tukey’s post hoc test. Results were considered significant if P<0.05. each rats in all group induced a progressive fever after 19 hour hour’s induction. Two among of three extract groups (hexane and ethanol extract) of each concentration (50, 100 and 200 mg/kg) demonstrated no significant difference (P<0.05) when compared to negative control. Different for aqueous extract of Ficus deltoidea which showed only two different doses ( 100 and 200 mg/kg), measured no significant difference (P<0.05) when compared to negative control whereas the lowest dose (50 mg/kg) showed significantly lower (P<0.05) than negative group for only at first, and four hour after treatment. For conclusion only aqueous extract Ficus deltoidea possess antipyretic properties for temporary effect while other two extractions (ethanol and hexane extract) possessed no antipyretic effect.